Incipient formation of zircon and hafnon during glass alteration at 90°C. Issue 6 (18th February 2019) - Calas, Georges; Galoisy, Laurence; Menguy, Nicolas; Jollivet, Patrick; Gin, Stéphane
Abstract: Layered zircon and hafnon are observed at the surface of gels resulting from the complete alteration of Zr‐ or Hf‐bearing borosilicate glasses at 90°C and pH 1. The unusually low temperature of formation may arise from the similarity of the local structure around Zr in the gel (from the altered glasses), the leaching solution and the zircon structure, in particular, the majority eight‐coordination of Zr and the connectivity of Zr‐sites with their surroundings. Similar behavior is expected for Hf, which mimics Zr speciation in solution and hafnon structure. This work expands the known formation methods of zircon and hafnon at low temperature, underlining the importance of amorphous precursors to facilitate crystal growth under unusual conditions.